2018
DOI: 10.1186/s13756-018-0441-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility among gram-positive and gram-negative blood-borne pathogens collected between 2012-2016 as part of the Tigecycline Evaluation and Surveillance Trial

Abstract: BackgroundAntimicrobial activity of tigecycline and comparator agents was assessedin vitroagainst 27857 isolates source from blood samples collected between 2012 and 2016 as part of the Tigecycline Evaluation and Surveillance Trial (TEST).MethodsThe broth microdilution methods was used to determine  minimum inhibitory concentrations (MIC) of blood-borne isolates according to guildlines of the Clinical and Laboratory Standards Institute (CLSI). Antimicrobial susceptibility breakpoints from CLSI guidelines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 28 publications
8
29
0
Order By: Relevance
“…For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [28]. Additionally, it was comparable to international rates [5,24], with exception of North and South American ones which traditionally have very high rates of VRE [8,9,24]. Despite the relatively low resistance of GPPs observed in the current and local studies, reports has warned from an increasing trend in the resistance of GPPs in Saudi Arabia, specially VRE, probably due to overuse of broad-spectrum antimicrobials and development of new resistance patterns [27,28].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [28]. Additionally, it was comparable to international rates [5,24], with exception of North and South American ones which traditionally have very high rates of VRE [8,9,24]. Despite the relatively low resistance of GPPs observed in the current and local studies, reports has warned from an increasing trend in the resistance of GPPs in Saudi Arabia, specially VRE, probably due to overuse of broad-spectrum antimicrobials and development of new resistance patterns [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…In addition to the low contribution, GPPs causing SSI in the current study were generally less resistant than reported internationally. For example, MRSA rates was 30% in the current study compared with more than 40% in USA [8,9], Europe [5], and Asia [24,25]. In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [26,27].…”
Section: Discussionmentioning
confidence: 75%
“…For VRE, the current rates (13%) was comparable to recent reports from Saudi Arabia [35]. Additionally, it was comparable to international rates [5,31], with exception of North and South American ones which traditionally have very high rates of VRE [14,15,31]. Despite the relatively low resistance of GPPs observed in the current and local studies, reports has warned from an increasing trend in the resistance of GPPs in Saudi Arabia, specially VRE, probably due to overuse of broad-spectrum antimicrobials and development of new resistance patterns [34,35].…”
Section: Discussionsupporting
confidence: 82%
“…In addition to the low contribution, GPPs causing SSI in the current study was generally less resistant than reported internationally. For example, MRSA rates was 30% in the current study compared with more than 40% in USA [14,15], Europe [5], and Asia [31,32]. In Saudi Arabia, there has been a great variability in the published MRSA rates, probably due to mixing community and hospital isolates as well as clinical and surveillance isolates [33,34].…”
Section: Discussionmentioning
confidence: 75%
“…34 The TEST study showed that Africa and Asia were the two regions of the world with the highest occurrence of S. aureus resistant to multiple antibiotics among blood-borne infections. 35 There is a plea for worldwide, automated, and comprehensive surveillance of antimicrobial resistance patterns. 8,36,37 Such surveillance could help optimize the worldwide use of antibiotics to improve infection control and minimize the occurrenceof resistant strains.…”
Section: Discussionmentioning
confidence: 99%